A framework for design and optimization of tapered composite structures. Part I: From individual panel to global blending structure. (15th October 2016) - Jing, Zhao; Sun, Qin; Silberschmidt, Vadim V.
Abstract: A novel framework to design tapered composite structures is proposed for buckling analysis with multiple manufacturing constraints, with variables dealt with separately at different levels and manufacturing constraints divided and imposed in each step. The framework is based on two techniques – a sequential permutation table (SPT) method and a global shared-layer blending (GSLB) method; a design concept is extending from an individual panel to the overall structure by improving its blending property. A problem to design an 18-panel tapered composite structure is adopted to study and validate the proposed framework; a detailed design process is executed step by step to demonstrate the improvements of blending property. Multiple manufacturing constraints are analyzed for the obtained optimal solution, which is also compared with previous studies. The high efficiency of the proposed framework implies its potential for design of large-scale composite structures with complex manufacturing constraints.